Optimization of Municipal Energy Systems with the Use of an Intelligent Analytical System = Optymalizacja miejskich systemów energetycznych przy wykorzystaniu inteligentnego systemu analitycznego - Ziembicki, Piotr; Klimczak, Marcin; Bernasiński, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the analytical and consultancy system which aims at a complex, comprehensive, multi-criteria energy performance analysis of a given building or a group of buildings and at making a recommendation for an energy source with regard to CO2 emission and investment costs determined on the basis of indicators included in the knowledge databases.
Keywords: energy system; simulation; optimization; analytical system; smart city; system energetyczny; symulacja; optymalizacja; inteligentne systemy analityczne; smart energy city